Study protocol: Worldwide comparison of vitamin D status of immigrants from different ethnic origins and native-born populations—a systematic review and meta-analysis - Yousef, Said; Elliott, Jesse; Manuel, Douglas; Colman, Ian; Papadimitropoulos, Manny; Hossain, Alomgir; Leclair, Nathalie; Wells, George A (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background A growing body of literature indicates that, worldwide, immigrants experience health deterioration after their arrival into their adopted country, and moreover, they have lower vitamin D compared to the native-born population. We plan to review if the levels of vitamin D are comparable between different ethnic groups in different regions of the world with those of native-born populations and to identify the possible associations between vitamin D deficiency and disease status among immigrants. Methods/design A systematic review and meta-analysis will be conducted following the methods of the Cochrane handbook for systematic reviews. A literature search was performed to identify studies on immigrants and vitamin D. The primary outcome is vitamin D levels, and the secondary outcome is any vitamin D deficiency-related disease. Study design and participant characteristics will be extracted, including ethnicity, country of birth and/or origin, and the host country. Descriptive and meta-analytic summaries of the outcomes will be derived. Distiller-SR and RevMan will be used respectively for data management and meta-analysis. Discussion This systematic review may partially help clarify vitamin D-related health deterioration in migrants; moreover, to develop a global guideline that specifies sub-populations, in which the evidence and vitamin D-related recommendations might differ from the overall immigrant population. Systematic review registration PROSPERO CRD42018086729